Caracterização do excesso de peso e do consumo alimentar na região sul do Brasil: uma análise do perfil epidemiológico alimentar e nutricional - Barancelli, Marcia Domênica Cunico (2023)
The negative impacts of the decline in food quality, both in the Brazilian population and in the world, show profound changes in people's health. Malnutrition, obesity and climate change interact synergistically forming the global syndemic, three pandemics that occur simultaneously in time and space, producing social consequences. Sizing the malnutrition that causes overweight and its relationship with food consumption, the object of this study, incorporates a systemic view of food and its impacts on health and the environment. Likewise, discussing access to adequate and healthy food contributes to the understanding of food systems. The general objective of the thesis is to understand the prevalence and temporal trend of overweight and food consumption based on the epidemiological profile of food and nutrition in the southern region of Brazil. The strategy of the epidemiological method with a quantitative approach, in this work, is classified as aggregated, observational, descriptive and analytical of ecological design and temporal trend. It is a population monitored by the Food and Nutrition Surveillance System (SISVAN), served by the Unified Health System (SUS), in the southern region of Brazil. Data were analyzed for nutritional status and food consumption by stages of the life cycle (children, adolescents, adults and elderly), sex for prevalence and temporal trend, in a historical series from 2015 to 2021. The research showed that the prevalence of overweight in the South region is above the national average in all stages of life, with the exception of children under 2 years of age. There was a higher prevalence of overweight in adults (71.2%), followed by elderly people (58.3%), children aged 5 to 9 years (41.1%), adolescents (40.4%), children from 2 to 4 years (37.1%), children aged 6 to 23 months (36.7%) and with a lower prevalence in children aged 0 to 6 months (23.9%). Among the states in the South region, RS had a higher prevalence of overweight in all stages of the life cycle, only in children aged 0 to 6 months was overweight prevalent in the state of SC. Regarding the relationship between overweight and the profile of food consumption, the study allows us to infer that the consumption of ultra-processed foods prevails over the consumption of fresh and minimally processed foods, in all stages of life, with the exception of children under 2 years of age, in which breastfeeding is a protective factor against obesity. It is noticed that there was a decrease in the consumption of beans in all stages of life analyzed, in contrast to the higher prevalence in the consumption of sweetened beverages among ultra-processed foods, with an increase in the habit of having meals watching television. Exclusive Breastfeeding (EBF) in children aged 0 to 6 months in the South region was 53.5%, above the national prevalence, however malnutrition persists despite low prevalence. Finally, there are similarities regarding the prevalence of overweight and the consumption of ultra-processed foods. The dismantling of the traditional food culture was evident in favor of a culture that interests the food industries. There is a need to promote sustainable food systems that result in greater and better Food and Nutrition Sovereignty and Security (SSAN) by promoting the ecological production (and consumption) of healthy food in line with human development.